Pengaruh Pendidikan Kesehatan Tentang Seks Pra Nikah terhadap Pengetahuan Remaja di SMA Negeri 1 Deli Tua - Huwaina Af’idah; Nisrina (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
The problem of reproductive health and adolescent sexuality in Indonesia is still neglected, this can be seen from the many cases of out-of-wedlock pregnancies, dating violence and high-risk abortions using drugs. And their knowledge about the risks of having sex is still low. This is due to a lack of information regarding sexuality and reproduction. This research aims to determine the influence of health education about premarital sex on the knowledge of adolescents at SMA Negeri 1 Deli Tua. This research uses an description quantitative research type with a quasi-experimental one group pretest-posttest design method with a total of 80 samples using the paired t-test statistical test. The results of the research show that there is an influence of health education about premarital sex on the knowledge of teenagers at SMA Negeri 1 Deli Tua with a value of 0.000 < 0.05. The conclusion in this study is that there is a difference in the average frequency of students' knowledge about premarital sex after being given health education. The suggestion in this research is that it is hoped that all parties, especially health services in the Health Promotion section, will always disseminate health education about premarital sex to teenagers in schools in order to prevent casual sex.